Efeito antinoceptivo da fotobiomodulação e da metformina na dor orofacial pós-cirúrgica de ratas ovariectomizadas - Martins, Aline Barbosa Teixeira (2019)
Orofacial pain is any pain related to soft and mineralized tissues of the oral cavity and face and has been studied in relation to a higher prevalence in females, possibly due to the hormonal character involved. Some therapies are being developed, such as physiotherapeutic resources (photobiomodulation, for example) and drug repositioning. The aim of this study was to evaluate the antinociceptive effect of photobiomodulation and metformin on postoperative orofacial pain in rats with hypoestrogenism. This was an experimental study conducted with Wistar rats separated into 12 groups (n = 6 / each) in different treatment categories. Hypoestrogenism was induced by bilateral ovariectomy (OVX). Vaginal cytologies were analyzed to observe the estrous cycle phase of each rat. After reaching the menopause stage, infraorbital nerve transection (IONX) surgery was performed. Sham and naive groups were included (n = 6 / each). The groups were treated with metformin (MET 250 mg / kg), red laser or infrared laser or resource combination for 14 consecutive days. At 10, 30, 50, 70, 100 and 140 postoperatively, the rats received acetone on the vibrissa to assess cold hypersensitivity. The number of facial rubbing was used as a nociception parameter. MET, control, sham and naive animals had their brain tissues collected and immunohistochemically analyzed with mTOR and ATF3 reagents. Infraorbital nerve transection promoted cold hypersensitivity in non-ovariectomized (non-OVX) and ovariectomized (OVX) rats from the 1st postoperative day until the 7th day, compared to sham and naive groups. On the 7th day, the OVX + IONX rats presented higher number of nociceptive behaviors (** p <0.01) compared to the group submitted to IONX surgery alone. The OVX and non-OVX rats treated with MET, red and infrared laser showed less nociceptive behavior when compared to OVX Control and OVX + IONX Control groups until the 7th postoperative day. There was no difference between the groups of OVX and non-OVX rats treated with red and infrared laser, except on the 7th postoperative day when the OVX rats decreased nociceptive behavior in relation to non-OVX group (**** p <0, 0001). The combination of MET and red or ;infrared laser prolonged the antinociceptive effect until the 10th postoperative day. MET reduced mTOR (** p <0.001) and ATF-3 (* p <0.05) signaling immunoexpression in brainstem and trigeminal ganglia. It was concluded that the red and infrared laser have antinoceptive effect in normal and ovariectomized rats when compared to the control group, and the analgesic effect was longer when the infrared laser was used. Metformin has a neuroprotective effect, leading to an analgesic character. Rats treated with red or infrared laser metformin showed reduced nociceptive behavior when compared to the control group, and this effect was prolonged when using infrared. There is no overlap of results when using the combination of metformin and red or infrared laser. Keywords: Orofacial